Pengaruh Model CIRC dan Teknik Close Reading Terhadap Membaca Kritis dalam Pembelajaran Bahasa Indonesia: Pada Siswa Kelas V Sekolah Dasar - Hermawati, Atit; Houtman, Houtman; Ardiasih, Lidwina Sri; Saabighoot, Yus Alvar (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
This study was conducted to determine the effect of the CIRC model and close reading techniques on critical reading literacy in Indonesian language subjects for 5th graders at SDN Perumnas Tangerang. This research was conducted with a population of 171 students. The research sample was 42 students with an explanation of 21 students in the experimental class and 21 students in the control class. The research instrument used an observation sheet and a test sheet. Data analysis using T-test. From the results of the CIRC class hypothesis test, it was found that tcount (3.556) > ttable (1.720). Hypothesis test results for the Close Reading class Sig. (2-tailed) < 0.05 that is 0.04 and t count (3.146) > t table (1.720). Anova test with sig = 0.000 <0.05, Fcount (8.309) > Ftable (4.325). The results of the analysis showed that there was an effect of the CIRC model and close reading technique on critical reading skills and the simultaneous effect of the CIRC model and close reading technique on students' critical reading ability.